(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
Shulamit Almog, The Origins of the Law in Homer [Law and Literature, 21], Berlin / Boston, de Gruyter, 2022, 142 S. ISBN: 978-3-11-076593-9.